Teacher Education Students' Pedagogical Content Knowledge: Retooling the Mentorship Process Within Schools of Education in Kenya - Rose Atieno Opiyo (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
The impact of globalization has brought changes to education which requires teachers to demonstrate practical pedagogical wisdom in critical features of teaching, namely: the subject matter being taught, the classroom context, and the physical and psychological characteristics of the students, that is, Pedagogical Content Knowledge (PCK). High level of Pedagogical Content Knowledge (PCK) leads to delivery of high-quality instruction in today's highly contextualized classroom settings and has the potential of producing learners who are prepared for a competitive society. However, teachers' lack of PCK has been identified as a pervasive problem all over the world. In Kenya, it has been highly linked to the recurrence of poor performance in local and internal competitive examinations, poor attitudes in some subjects, and lack of motivation for continuous learning among school-age children along the education continuum. Even so, the voice of student teachers and that of the school practice advisors, at the center and apex of this mentorship process in the Universities, has been largely ignored in transformative teacher education discourse. Guided by literature on transformative teacher education, student teacher mentorship, and reflective pedagogy, this paper presents the perspectives of 50 Student Teachers (STs) and 10 School Practice Advisors. STs confidence in special teaching methods courses, pedagogical content competence in teaching both independently and collaboratively, key areas of concern for PCK improvement, and practical strategies for PCK mentorship were the focus. Based on a qualitative and an interpretive research paradigm, the sentiments of 50 STs who participated in the May-August, 2017 School Practice as well as the views of 10 School Practice Advisors (SPAs) from the School Education (SEDU) of Masinde Muliro University of Science and Technology were sought. Based on four domains of Pedagogical Content Knowledge (PCK) which include  Subject Matter Knowledge (SMK), Knowledge of Curriculum (KoC) and Knowledge of Learners (KoL), and Knowledge of Pedagogies (KoP), the paper provides insights for teacher educators and University Management on areas that need further improvement and strategies for developing beginning teachers' PCK practices.